Developing the learning achievement of students in the English subject "Where are you from" using games for Mathayom 1 students at Jaraphattwittaya Secondary School Sikhoraphum District, Surin Province - Laowaranyu, Termphong (Academic Journal of Local Development, 2024)
The purpose of this research was to compare the learning outcomes of English vocabulary before and after learning of Mathayom 1 students. Janaphat Witthaya Secondary School Learned from the learning management plan using games and to compare the English vocabulary abilities of Mathayom 1 students. 1Before studying and after studying using games The tools used in the research were: 1) a learning management plan on academic achievement of students in the English subject "Where are you from?" Using games for Mathayom 1 students at Jaraphattwittaya High School. It is a learning management plan created and developed by the researcher. to develop abilities English vocabulary using games 2) Pre-study and post-study English tests For Mathayom 1 students, it is a test created by the researcher with 20 questions. Statistics used in data analysis include The mean and standard deviation of the research results were found that Academic achievement of students in the English subject "Where are you from?" using games for Mathayom 1 students at Jaraphattwittaya High School The academic results before studying had an average score of 5.54. The academic results after studying had an average score of 9.54 when testing the difference in means. It was found that the results of learning English vocabulary using games after learning were significantly higher than before learning Statistical significance at the level 0.05 and students’ opinions on using games to develop English vocabulary learning were at a like level. The mean is 4.70 and the standard deviation is 4.70